Ly9 (CD229) Cell-Surface Receptor is Crucial for the Development of Spontaneous Autoantibody Production to Nuclear Antigens - de Salort, Jose; Cuenca, Marta; Terhorst, Cox; Engel, Pablo; Romero, Xavier (Frontiers in Immunology, 2013)
The Signaling Lymphocyte Activation Molecule Family (SLAMF) genes, which encode cell-surface receptors that modulate innate and adaptive immune responses, lay within a genomic region of human and mouse chromosome 1 that confers a predisposition for the development of systemic lupus erythematosus (SLE). Herein, we demonstrate that the SLAMF member Ly9 arises as a novel receptor contributing to the reinforcement of tolerance. Specifically, Ly9-deficient mice spontaneously developed features of systemic autoimmunity such as the production of anti-ANA, -dsDNA and -nucleosome autoantibodies, independently of genetic background ([B6.129] or [BALB/c.129]). In aged [10-12 month old] Ly9-/- mice key cell subsets implicated in autoimmunity were expanded, e.g. T follicular helper (Tfh) as well as germinal center (GC) B cells. More importantly, in vitro functional experiments showed that Ly9 acts as an inhibitory receptor of IFN-g producing CD4+T cells. Taken together, our findings reveal that the Ly9 receptor triggers cell intrinsic safeguarding mechanisms to prevent a breach of tolerance, emerging as a new non-redundant inhibitory cell-surface receptor capable of disabling autoantibody responses.